The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.0022-202x.2001.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Melanoma Cell Proliferation by Histidine Decarboxylase Specific Antisense Oligonucleotides

Abstract: Histidine decarboxylase (HDC) is expressed by the cells of melanoma, in which the histamine content tends to be relatively high. This study shows that elevated expression of HDC was found by western blot analysis of primary and metastatic melanoma tissue using a polyclonal HDC specific antibody. The specificity of anti-HDC antibody was confirmed by inhibition of HDC translation (i.e., immunopositivity) in melanoma cells by HDC-specific antisense oligonucleotide. Moreover, the decrease in proliferation caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…Therefore, histidine decarboxylase can serve as a specific marker for biosynthesis of histamine. It has been shown that levels of mRNA encoding histidine decarboxylase, histidine decarboxylase protein expression, and enzymatic activity are significantly increased in both experimental and human tumors, such as melanoma (3,4), small cell lung carcinoma (5), breast carcinoma (6), endometrial cancer (7), and colorectal carcinoma (8). These data suggest that histamine may be directly involved in tumor development and progression.…”
mentioning
confidence: 74%
“…Therefore, histidine decarboxylase can serve as a specific marker for biosynthesis of histamine. It has been shown that levels of mRNA encoding histidine decarboxylase, histidine decarboxylase protein expression, and enzymatic activity are significantly increased in both experimental and human tumors, such as melanoma (3,4), small cell lung carcinoma (5), breast carcinoma (6), endometrial cancer (7), and colorectal carcinoma (8). These data suggest that histamine may be directly involved in tumor development and progression.…”
mentioning
confidence: 74%
“…As melanoma tumors are known to overexpress HDC, thereby releasing large amounts of histamine, an inflammatory mediator in their microenvironment, the clarification of the consequences of this phenomenon is of imperative importance. Although in previous in vitro studies, we and others have repeatedly suggested a possible involvement of neoplastic histamine secretion in melanoma tumor progression (15,(27)(28)(29), there were only sparse in vivo data available, providing rather indirect evidence for this concept (30).…”
Section: Discussionmentioning
confidence: 99%
“…The mast cell-derived mediators, such as histamine, tryptase, bFGF, VEGF, and IL-8, are shown to enhance tumor growth and angiogenesis. The studies have shown that an inhibition of histidine decarboxylase, a key enzyme involved in histamine synthesis, is associated with attenuation of cancer proliferation (Hegyesi et al 2001) and thus suggesting that histamine acts as an autocrine growth factor to regulate the cell proliferation (Lampiasi et al 2007). In lung adenocarcinoma, the number of mast cells has been directly correlated with tumor angiogenesis and poor prognosis (Ch'ng et al 2006;Imada et al 2000).…”
Section: Cancermentioning
confidence: 98%